Upaya Peningkatan Reduksi Sampah Melalui Bank Sampah dengan Pendekatan Structural Equation Modelling (Studi Kasus : Bank Sampah Kecamatan Indihiang) - Rezia Asmiati Syifa; IDAA Darmadewanthi (Jurnal Serambi Engineering, 2024)
Waste generation in Tasikmalaya City reached 323,156 kg/day. Waste bank is a programme as an effort that can be done to reduce waste generation. Tasikmalaya has 74 waste bank units, 4 of which are in Indihiang district. According to the Environmental Department, the waste generation in Indihiang District is 25,664 kg/day. It's not yet known for sure how much waste reduction potential this programme has. Therefore, structural equation modelling (SEM) is used to analyse it. SEM is a method for processing data from questionnaires to determine the influence of the community's role in reducing waste through waste banks. The data results from the SEM method are processed using SmartPLS. The results show that the waste reduction potential through waste banks in Indihiang is currently 0.15%, but it can still be increased to 15% by increasing the number of waste bank customers. According to the SEM-PLS result, there is a significant influence between people's knowledge and behaviour on waste reduction, but in the aspect of people's attitude, the attitude of non-customers does not have a significant influence on waste reduction.